Aplicação do modelo de gestão em rede organizacional às políticas públicas de segurança : o caso da política de integração do sistema de Defesa Social de Minas Gerais - Figueiredo, Amanda Mátar de (2014)
The Government of the State of Minas Gerais implemented from 2003 a set of actions, restructuring institutions and governance of the public safety policy, which sets out the institutional arrangement called "Social Defense System" and public policy called "Integration Policy of Social Defense System". Innovation in governance was assigned to horizontal and collegiate model, driven policy that works within the establishment, for all interventions, of thematic integrated instances. This dissertation proposes an analysis of the conformation of the Integration Policy, from references of the fields of public management and neo-institutionalism theory, concerning the dynamics of the network and the construction of legitimacy. The intention was to analyze relevant issues to the present model of governance of public security, which refer not only to the trajectory and characteristics of the formation of organizational network, as well as its intersection with aspects of the institutional context. Qualitative methodology was applied, combining descriptive and exploratory elements from literature and documents from secondary sources, composed of the documents produced by the Social Defense System in the context of projects and activities of the Integration Policy (legislation, documents, technical reports, etc.), as well as a set of semi-structured interviews and workshops conducted by João Pinheiro Foundation for the project of the 2013-2015 State Plan for Social Defense. The conclusion is that, in a context strongly marked by path dependency, disarticulation, imbalances of power and legitimacy, the application of network governance demonstrated a potentially qualified path to institutionalize dialogue and seek more objective parameters to the minimum necessary coordination implementation of built and run multi-managed policies, such as the public safety policies in Minas Gerais.